Implementasi Segregasi Kelas Berbasis Gender Dalam Menaggulangi Interaksi Negatif Siswa Di SMP Al-Falah Ketintang Surabaya - Zaini Tamin AR; Subaidi Subaidi (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, So far segregation has often been used in social sciences as an effort to resolve social conflicts without harming either party. Through this article, the author seeks to use class segregation in the world of education. In this case, this article analyzes the implementation of gender-based class segregation in overcoming negative student interactions in relation to the process of religion-based education (Islam) in Al-Falah Surabaya Middle School. With a descriptive-qualitative approach, this article argues that the application of gender-based class segregation needs to be done in a gradual and sustainable manner in which strict rules and regulations apply. In this context, leaders, teachers, guidance counseling (BK) teachers must work together in providing continuing coaching of students in matters of religion, because religion is a force that will foster positive energy. By implementing the system, Al-Falah Middle School students get a complete religion-based education (Islam); education is not only on the theoretical aspects, but also applicable to everyday life.Keywords: Segregation, Gender, Islamic Education, Student Negative Interaction